Beyond the West and Beyond the Canon – Feminist Ecocriticism Today (KULT_online, 2018)
Current controversies around the Anthropocene concept and global climate justice underline what many ecofeminist scholars, and specifically postcolonial ecofeminists, have been stressing for decades: The ongoing suppression of female and queer voices and bodies is not only deeply intertwined with racism and colonial violence, but also with the destruction of nature through those same forces and histories. There is a need for intersectional approaches and voices which take the multiple dimensions of human and non-human experience seriously; a gap which this present edited volume, Literature and Ecofeminism, Intersectional and International Voices by Douglas A. Vakoch and Sam Mickey sets out to fill. It offers a number of insightful and careful analyses of literature and covers a lot of ground, both historically and geographically.